"Internet Witch Hunt" is the Sharp Edge of the Internet Era: – Based on Python Analysis of the Public Opinion and Emotional Analysis of "Online Witch Hunting" by Mainstream Media and Online Social Media - Xue, Yi (Transactions on Social Science, Education and Humanities Research, 2024)
In the Internet era, personal freedom of speech has been fully reflected, but it has also brought a lot of negative effects."Internet witch hunting" refers to human flesh search, information collection, personal attacks on specific people on the Internet, and stirring people’s emotions through the Internet. In recent years, with the development of the Internet, Internet rumors and online violence and other phenomena began to spread on the Internet. On online social media platforms, personal freedom of speech has been fully reflected, but it has also brought great hidden dangers to public security. With the development of technology, personal privacy has been paid more and more attention. How to protect personal privacy and prevent network violence has become a common problem in today’s society. Starting from Python language, this paper will analyze the content of word frequency, word cloud map, theme modeling, emotion analysis results of mainstream media and social platforms for "online witch hunt" events, so as to provide a certain reference for us to better protect the personal privacy of ourselves and others.